Non-coding RNAs in the brain: new class of prospective biomarkers and therapeutics - Goel, Rajeev (International Journal of Research in Medical Sciences, 2023)
The human genome encrypts around 20,000 protein coding genes, constituting around 1% of the total human genome sequence. The rest of it initially labeled as a “junk DNA” is transcribed to a distinct class of non-coding RNAs (ncRNAs) which do not code for any protein in the cell and their presence was quite intriguing to the researchers. The recent studies, however, have surprisingly revealed the vital roles of these ncRNAs in regulating an array of diverse cellular and biological processes in different organs including brain. The dysfunction of these regulatory ncRNAs in human brain causes certain neurological disorders and brain tumors which earlier have been widely linked to various risk factors such as oxidative stress, genetic mutations, aberrant protein degradation and dysfunctional neural network. This review provides an overview of different types of ncRNAs, their regulatory roles in brain functions and neurological disorders along with their prospects to be used as potential biomarkers and therapeutics.